Metamotivation in medical students: Explaining motivation regulation strategies in medical students - Ali Norouzi; Maryam Alizadeh; Dean Parmelee; Saharnaz Nedjat; Saiideh Norouzi; Mohammad Shariati (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Metamotivation is a process that students use to monitor their motivational states to reach their academic goals. To date, few studies have addressed the ways that medical students manage their motivational states. This study aim to identify the motivational strategies of medical students as they use the metamotivational process to monitor and control their motivational states. MATERIALS AND METHODS: This qualitative study uses directed content analysis of the narrative responses of 18 medical students to draft an in-depth and semistructured interview protocol which were conducted through WhatsApp due to social distance restrictions of COVID-19. Data were collected, encoded, and analyzed using deductive content analysis approach descripted by Elo and Kyngäs. RESULTS: Seven main themes were extracted as the motivational strategies of medical students including "regulation of value," "regulation of situational interest," "self-consequating," "environmental structuring," "efficacy management," "regulation of relatedness," and "regulation of situational awareness." In this study by identifying new strategies, we provide a broader framework of metamotivational strategies in the field of the progression of learners in medical education. CONCLUSION: Medical students use a variety of strategies to regulate their academic motivation. To sustain and improve the motivation of medical students, identifying and strengthening metamotivational strategies is the first step.